2013
DOI: 10.1377/hlthaff.2012.1072
|View full text |Cite
|
Sign up to set email alerts
|

State Insurance Exchanges Face Challenges In Offering Standardized Choices Alongside Innovative Value-Based Insurance

Abstract: Value-based insurance is a relatively new approach to health insurance in which financial barriers, such as copayments, are lowered for clinical services that are considered high value, while consumer cost sharing may be increased for services considered to be of uncertain value. Such plans are complex and do not easily fit into the simplified, consumer-friendly comparison tools that many state health insurance exchanges are formulating for use in 2014. Nevertheless some states and plans are attempting to stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Thus, this increase in cost‐sharing is less controversial and less complex to employ than in situations where treatments must be authorized by physicians. Some state programmes have tied higher cost‐sharing to preference‐sensitive interventions, a strategy that is trying to orient cost‐sharing to interventions of questionable clinical value.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this increase in cost‐sharing is less controversial and less complex to employ than in situations where treatments must be authorized by physicians. Some state programmes have tied higher cost‐sharing to preference‐sensitive interventions, a strategy that is trying to orient cost‐sharing to interventions of questionable clinical value.…”
Section: Discussionmentioning
confidence: 99%
“…enacting tort reform; and many other strategies. 44,45 Legislation 1. State governments should take steps to make the knowledge of prices for services at various institutions readily available to the public and primary care offices.…”
Section: Insurance Company Administrative Policiesmentioning
confidence: 99%
“…Minimizing confusion is vital since our research found that persons in this age range do not understand the notion of a premium, or how it is distinguished from a co-payment. Research also suggests that a simulator, in which consumer's responses to hypothetical scenarios are used to steer them towards health insurance options, may be useful (Corlette, Downs, Monahan, & Yondorf, 2013). Ultimately the goal is for young consumers to match their perceived need for health insurance to a health insurance plan and our recommendations are intended to inform the organizations and individuals (e.g., navigators) who facilitate this.…”
Section: Implications For Policymentioning
confidence: 99%